Active noise control - a review of control-related problems - PAWEŁCZYK, Marek (Archives of Acoustics, 2008)
Active noise control is a research area, where both acoustic and control related problems influence success of applications. The aim of the paper is to address the control aspects. After introducing active noise control in general, the fundamental state of the art is presented. The possible control techniques are discussed. Premises for the choice of feedforward, feedback and combined architectures are summarised. Single-channel and multi-channel systems are confronted. Benefits and drawbacks of continuous-time and discrete-time approaches are emphasised. Fixed-parameter and adaptive control systems are referenced. General control system requirements are formulated. Fundamental performance limitations are explained. Various control problem formulations including cost functions and constraints are presented for an exemplary structure.